2010
DOI: 10.3382/ps.2010-00987
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to dietary β-glucan in broiler chicks during an Eimeria challenge

Abstract: Escalating consumer concerns regarding pathogen resistance have placed the poultry industry under mounting pressure to eliminate the use of chemotherapeutic agents as feed additives. One possible alternative receiving increased attention is the use of immunomodulators such as β-glucan. A study was conducted to investigate the effects of a yeast-derived β-glucan (Auxoferm YGT) on broiler chick performance, lesion scores, and immune-related gene expression during a mixed Eimeria infection. Day-old chicks were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 27 publications
7
63
0
7
Order By: Relevance
“…Accurate assembly of the mucin genes is difficult due to the large size of the central tandem repeats [39], which is probably why attempts to fully sequence the mucin genes in this study were unsuccessful. Carp mucin sequences had high homology to two mammalian and avian gel forming mucins:Muc2 and Muc5B.…”
Section: Homology Of Carp Mucin With Vertebrate Mucinsmentioning
confidence: 97%
See 1 more Smart Citation
“…Accurate assembly of the mucin genes is difficult due to the large size of the central tandem repeats [39], which is probably why attempts to fully sequence the mucin genes in this study were unsuccessful. Carp mucin sequences had high homology to two mammalian and avian gel forming mucins:Muc2 and Muc5B.…”
Section: Homology Of Carp Mucin With Vertebrate Mucinsmentioning
confidence: 97%
“…Consistent, but not significant, down-regulation of Muc2 in the intestine and gills was seen in the glucan fed fish, while Muc5B was significantly increased in skin, with slight up-regulation in gills. An up-regulation of Muc2 expression after b-glucan feeding was described in the intestine of chicken [39] and pigs [40], and an increased expression of Muc2 and Mub5B has been observed in mammals after bacterial [35,41e43] and nematode infections [44].…”
Section: Organism: Latin Namementioning
confidence: 98%
“…The present study has been conducted using an experimental protocol similar to that of some recent reports (Cox et al, 2010;Orengo et al, 2012;Kim et al, 2013;Scheurer et al, 2013). In this study, the birds were inoculated with E. acervulina and E. tenella, while Kim et al (2013) showed that E. maxima was more effective in reducing weight gain than E. tenella.…”
Section: Discussionmentioning
confidence: 97%
“…In a subsequent study involving a mixed Eimeria infection at 8 days of age, intestinal iNOS expression was down-regulated in the ileums of 0.1% b-glucan fed birds in the absence of a challenge, but upregulated in the challenged, b-glucan treated birds. These results suggest a dynamic function of bglucans dependent on the disease status (Cox et al, 2010b).…”
Section: Effects Of B-glucans On the Innate Immune Responsementioning
confidence: 97%